Gut microbiota-derived indoleacetic acid attenuates neuroinflammation and neurodegeneration in glaucoma through ahr/rage pathway - Ning Wang; Chengyang Sun; Yijie Yang; Dandan Zhang; Lulu Huang; Chenrui Xu; Minghan Wang; Mengmeng Xu; Tongtong Yan; Yue Wu; Li Xu; Yahan Ju; et al. (Journal of Neuroinflammation)
Abstract Background Gut microbiota has emerged as a promising therapeutic target for neurodegenerative disorders through regulation of neuroinflammatory responses, while its role in optic nerve degeneration remains incompletely characterized. This study elucidates the neuroprotective role of gut microbiota derived tryptophan metabolites in glaucoma through gut-eye communication and inhibition of microglia-mediated neuroinflammation. Methods Gut microbiota profiling (16 S rRNA sequencing) and serum indoleacetic acid (IAA) quantification were performed in glaucoma patients versus controls. Microbiota–metabolite relationships were further validated through fecal microbiota transplantation (FMT). The neuroprotective and anti-neuroinflammatory effect of Bacteroides fragilis (B. fragilis) and IAA was assessed in both microbead-induced ocular hypertension mice model and in vitro BV-2 microglial cell inflammation model via immunofluorescence, qPCR, Western blot and mice behavioral assays. To explore the underlying mechanisms, retinal transcriptomics and microglia-neuron co-cultures were also employed. Result Glaucoma patients exhibited gut dysbiosis characterized by depleted tryptophan-metabolizing bacteria (B. fragilis, Bacteroides thetaiotaomicron, Anaerostipes hadrus) and reduced serum IAA levels. Mice receiving FMT from glaucoma patients exhibited lower systemic IAA levels. In in vivo and in vitro models, B. fragilis or IAA restored AhR activation, suppressed inflammation by inhibiting microglial activation and the release of pro-inflammatory mediators throughout the retina, reduced retinal ganglion cells (RGCs) loss and preserved visual function. Mechanistically, IAA attenuated RAGE/NF-κB pathway activation via AhR-dependent signaling, conferring neuroprotection. Conclusion Our study proposes a novel AhR-mediated gut microbiota-eye axis in glaucoma pathogenesis and demonstrates that IAA serves as an effective neuroprotective strategy with clinical potential for managing RGCs neurodegeneration.